2022
DOI: 10.1002/cpe.7296
|View full text |Cite
|
Sign up to set email alerts
|

Deep neural network based interactive fuzzy Bayesian search algorithm for low‐cost smart farming automation model

Abstract: Summary One of the most significant factors that influence the globalized economy is agriculture. In order to address the requirement of increasing populations in terms of food necessities, modernizations and technological progressions in agriculture, it is necessary to implement a smart agricultural system. Various traditional techniques are still utilized by the farmers and their intuition in agriculture is not enough to furnish and deliver various issues namely soil management, plant disease identification,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…Numerous studies have succeeded in predicting agricultural yield, and AI can be observed as a good prediction method. AI comprises neural network models like the artificial neural network (ANN) (Esfe, Kamyab, and Toghraie 2022), deep neural network (DNN) (Sivaraj and Palanisamy 2022) and machine learning (ML) (Reddy and Kumar 2021) models like the random forest (RF) (Yang et al 2021), K-nearest neighbour (KNN) and support vector machine (SVM) (Dang et al 2021). There were many crop yield prediction algorithms based on ML, including deep reinforcement learning, hybrid convolutional neural network (CNN)-long short term memory (LSTM) architecture, hybrid MLR-ANN architecture (Mythili and Rangaraj 2021) and the CNN-Recurrent neural network (RNN) framework.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have succeeded in predicting agricultural yield, and AI can be observed as a good prediction method. AI comprises neural network models like the artificial neural network (ANN) (Esfe, Kamyab, and Toghraie 2022), deep neural network (DNN) (Sivaraj and Palanisamy 2022) and machine learning (ML) (Reddy and Kumar 2021) models like the random forest (RF) (Yang et al 2021), K-nearest neighbour (KNN) and support vector machine (SVM) (Dang et al 2021). There were many crop yield prediction algorithms based on ML, including deep reinforcement learning, hybrid convolutional neural network (CNN)-long short term memory (LSTM) architecture, hybrid MLR-ANN architecture (Mythili and Rangaraj 2021) and the CNN-Recurrent neural network (RNN) framework.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have succeeded in predicting agricultural yield, and AI can be observed as a good prediction method. AI comprises neural network models like the artificial neural network (ANN) (Esfe, Kamyab, and Toghraie 2022), deep neural network (DNN) (Sivaraj and Palanisamy 2022) and machine learning (ML) (Reddy and Kumar 2021) models like the random forest (RF) (Yang et al. 2021), K‐nearest neighbour (KNN) and support vector machine (SVM) (Dang et al.…”
Section: Introductionmentioning
confidence: 99%